Isolation of pathogenic bacteria from sputum samples using a 3D-printed cartridge system - Pahlow, Susanne; Hentschel, Stefanie; Horbert, Peter; Romero, Cynthia; Lehniger, Lydia; Wagner, Sascha; Popp, Jürgen; Weber, Karina (Analytical Methods, 2021)
Within this contribution we introduce a 3D-printed cartridge system enabling the convenient and cost-efficient sample preparation from sputum for subsequent PCR based detection schemes. The developed fluidic system operates on pneumatic actuations. The closed system ensures a very low probability for contamination during sample processing, which is crucial when using a highly sensitive detection method such as PCR. The enrichment of the bacterial cells is achieved using different types of amine-functionalized particles. Our particle-based sample preparation approach yields intact and viable bacterial cells. Accordingly, not only PCR-based detection schemes can be employed, but also spectroscopic methods and biochemical tests, which require cultivation steps, are possible. The cartridge design in principle is compatible with magnetic and non-magnetic particle types. We investigated both variants and found that the performance of expanded glass beads is superior over the magnetic particles within the cartridge. Owing to the rather large size of the expanded glass beads, the dimensions of the channels can be enlarged, leading to lower hydrodynamic resistances, which is beneficial when processing viscous samples such as sputum. We verified the performance of our system using both artificial and real sputum samples containing Escherichia coli and Moraxella catarrhalis.
CRIS-Team Scopus Importer:2023-04-20